Statistical analysis of muscle-actuated manipulators - Galhano, Alexandra (1992)
Joint-actuated robots have poor performances due to the high requirements imposed by the transients of the operational tasks. Muscle-actuated arms are superior because the anatomic levers adapt the manipulating exigencies to the driving actuators, The statistical analysis of these systems highlights its main properties and constitutes a step towards the design of new mechanical biological-like robotic structures.